Decellularized Tissues for Wound Healing: Towards Closing the Gap Between Scaffold Design and Effective Extracellular Matrix Remodeling - Solarte David, Víctor Alfonso; Güiza-Argüello, Viviana Raquel; Arango-Rodríguez, Martha L.; Sossa, Claudia L.; Becerra-Bayona, Silvia M. (Frontiers in Bioengineering and Biotechnology, 2022)
The absence or damage of a tissue is the main cause of most acute or chronic diseases and are one of the appealing challenges that novel therapeutic alternatives have, in order to recover lost functions through tissue regeneration. Chronic cutaneous lesions are the most frequent cause of wounds, being a massive area of regenerative medicine and tissue engineering to have efforts to develop new bioactive medical products that not only allow an appropriate and rapid healing, but also avoid severe complications such as bacterial infections. In tissue repair and regeneration processes, there are several overlapping stages that involve the synergy of cells, the extracellular matrix (ECM) and biomolecules, which coordinate processes of ECM remodeling as well as cell proliferation and differentiation. Although these three components play a crucial role in the wound healing process, the ECM has the function of acting as a biological platform to permit the correct interaction between them. In particular, ECM is a mixture of crosslinked proteins that contain bioactive domains that cells recognize in order to promote migration, proliferation and differentiation. Currently, tissue engineering has employed several synthetic polymers to design bioactive scaffolds to mimic the native ECM, by combining biopolymers with growth factors including collagen and fibrinogen. Among these, decellularized tissues have been proposed as an alternative for reconstructing cutaneous lesions since they maintain the complex protein conformation, providing the required functional domains for cell differentiation. In this review, we present an in-depth discussion of different natural matrixes recently employed for designing novel therapeutic alternatives for treating cutaneous injuries, and overview some future perspectives in this area.